Green Technique for the Extraction of Acid Soluble Collagen from Basa Fish (Pangasianodon hypothalmus) - Pradana, Adit Ludfi; Niamnon, Nakorn; Thanasupsin, Sudtida Pliankarom (Proceedings of the International Conference on Green Technology, 2019)
Basa fish (Pangasianodon hypopthalmus) is the top  fifth most consumed fish in Thailand. The production of Basa fish generates a large number of by-products. Nowadays, most of these residues are recovered as animal feedstocks or fertilizer. However, it is interesting to explore another choice of waste management practice such as the recovery of valuable material.  This study aimed to extract collagen from the skin and bone of  Basa fish (Pangasianodon hypopthalmus) by using a green  solvent. Two extraction methods were carried out. First, the  conventional extraction was conducted by using acetic acid and compared with the physical extraction which employed water  acidified with carbon dioxide. Conventional extraction was  conducted using 0.75 M acetic acid at 4oC and solid-liquid ratio 1:40 (w/v). The physical extraction using water acidified by carbon dioxide was conducted at 37oC, 10 bars and solid-liquid ratio 1:40 (w/v). The extraction time of each technique was varied from 3 to 24 hours. The FTIR results confirmed the presence of amide A, amide B, amide I, amide II, and amide III of the extracted collagen obtained from these two techniques. When using fish skin and bone as raw material, the physical extraction technique increased the yield of dry weight collagen by 8 times and 7 times, respectively. Additionally, the physical extraction could shorten the processing time (from pretreatment until freeze-drying) by 56 hours.